Cyber risk management for wireless communication in organization - Mutakin, Darul; Mohd Niyaz Khan, Mohd Toriq Khan; Ibrahim, Jamaludin (IJSRP INC., 2016)
This paper will discuss the current cyber threats in organization wireless network since it is a trend nowadays to implement wireless network in an organization. Despite the benefits that wireless technology can provide to organization, it also can bring potential cyber threats which are done in a form of sophisticated and diverse attacking mechanisms that will jeopardize the organization reputation. The BYOD initiative in organization has brought significant cyber risk and threats into the organization because of tremendous possession of mobile and portable devices by employees which can also utilized during work. The organization wireless network is accessible by the employees but at the mean time they bring potential cyber threats to the organization’s wireless network due to negligence of security policy on their devices, lack of security awareness, differences in device’s technology, inappropriate network configuration and advance attacking techniques. In this paper, some recommendation will be provided to readers in dealing with wireless cyber risk and threats in order to come out with sufficient cyber risk management plan for an organization.